Revenge of the tipping point : overstories, superspreaders, and the rise of social engineering - Gladwell, Malcolm, 1963- (London : Abacus Books, 2024)
"Revisits the world of social epidemics first explored in Gladwell's 2000 book 'The tipping point,' this time taking a closer look at the dark side of social engineering. Twenty-five years after the publication of his groundbreaking first book, Malcolm Gladwell returns with a brand-new volume that reframes the lessons of The Tipping Point in a startling and revealing light. Why is Miami... Miami? What does the heartbreaking fate of the cheetah tell us about the way we raise our children? Why do Ivy League schools care so much about sports? What is the Magic Third, and what does it mean for racial harmony? In this provocative new work, Malcolm Gladwell returns for the first time in twenty-five years to the subject of social epidemics and tipping points, this time with the aim of explaining the dark side of contagious phenomena. Through a series of riveting stories, Gladwell traces the rise of a new and troubling form of social engineering. He takes us to the streets of Los Angeles to meet the world's most successful bank robbers, rediscovers a forgotten television show from the 1970s that changed the world, visits the site of a historic experiment on a tiny cul-de-sac in northern California, and offers an alternate history of two of the biggest epidemics of our day: COVID and the opioid crisis. Revenge of the Tipping Point is Gladwell's most personal book yet. With his characteristic mix of storytelling and social science, he offers a guide to making sense of the contagions of modern world. It's time we took tipping points seriously."-- Provided by publisher.
Introduction. The passive voice -- I. Three puzzles. Casper and C-Dog -- The trouble with Miami -- Poplar Grove -- II. The social engineers. The magic third -- The mysterious case of the Harvard women's rugby team --Mr. Index and the Marriott outbreak -- III. The overstory. The L.A. survivors' club -- Doing time on Maple Drive -- IV. Conclusion. Overstories, superspreaders, and group proportions.
Includes bibliographical references (pages 309-338) and index.
Malcolm Gladwell is the author of seven New York Times bestsellers: The Tipping Point, Blink, Outliers, What the Dog Saw, David and Goliath, Talking to Strangers, and The Bomber Mafia. He is also the cofounder of Pushkin Industries, an audio-content company that produces Revisionist History, among other podcasts and audiobooks. He was born in England, raised in Canada, and lives outside New York with his family and a cat named Biggie Smalls.
Keywords: Social engineering; Social psychology; Contagion (Social psychology); Causation; Context effects (Psychology); Epidemics; Psychology, Social; Social sciences; Social psychology; Causation; Epidemics; Informational works; Informational works